Handbook of nonlinear optics - Sutherland, Richard L. ([S.l.] : CRC Press, 2014)
Examining classic theories, experimental methods, and practical formulas for exploration of the core topics in nonlinear optics, the second edition of this acclaimed text was extensively revised to reflect recent advances in the analysis and modification of material properties for application in frequency conversion, optical switching and limiting, multiphoton absorption, and electro-optic effects. Handbook of Nonlinear Optics, Second Edition contains additional chapters on ultrafast characterization techniques, laser flash photolysis, and the electro-optic effect as well as expanded coverage of nonlinear optics in fibers and pulsed two-beam coupling.